2013
DOI: 10.1007/s00248-013-0314-0
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Populations of the Aphid Aphis craccivora Are Infected with Diverse Facultative Bacterial Symbionts

Abstract: Facultative bacterial endosymbionts can play an important role in the evolutionary trajectory of their hosts. Aphids (Hemiptera: Aphididae) are infected with a wide variety of facultative endosymbionts that can confer ecologically relevant traits, which in turn may drive microevolutionary processes in a dynamic selective environment. However, relatively little is known about how symbiont diversity is structured in most aphid species. Here, we investigate facultative symbiont species richness and prevalence amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
88
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 73 publications
9
88
3
Order By: Relevance
“…Despite the limited H. defensa strain diversity identified in Ap. craccivora, facultative symbionts may still comprise much of the ecologically relevant heritable genetic variation present in these populations given the likely anholocyclic nature of this aphid in North America (44). The overall lack of allelic diversity uncovered in our microsatellite analysis (Table 3) is consistent with limited sexual reproduction such that a few related clones, with and without particular symbiont infections, may recolonize the North American range seasonally from overwintering source populations.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Despite the limited H. defensa strain diversity identified in Ap. craccivora, facultative symbionts may still comprise much of the ecologically relevant heritable genetic variation present in these populations given the likely anholocyclic nature of this aphid in North America (44). The overall lack of allelic diversity uncovered in our microsatellite analysis (Table 3) is consistent with limited sexual reproduction such that a few related clones, with and without particular symbiont infections, may recolonize the North American range seasonally from overwintering source populations.…”
Section: Discussionsupporting
confidence: 63%
“…craccivora is infected with the heritable facultative symbiont H. defensa, which confers protection against some species of parasitic wasps (37,38). Despite clear benefits to infection in the presence of wasps, however, this symbiont is found only at intermediate frequencies in natural populations (44,45). In this study, we identified clear costs to infection and maternal transmission failures associated with this protective symbiont, which likely constrain H. defensa spread in natural populations.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A phids harbor two types of bacterial endosymbionts: the obligate symbiont Buchnera aphidicola, which occurs in almost all aphids, and facultative bacteria belonging to a variety of taxa that are not essential for aphid survival and typically are found in some but not all individuals of a population (1)(2)(3). The association between Buchnera and aphids was established 80 to 150 million years ago (4), and because transmission is strictly maternal, bacteria and host phylogenies are perfectly congruent.…”
mentioning
confidence: 99%
“…It should be noted that, considering the relatively small sample sizes subjected to cloning and sequencing of the bacterial 16S rRNA gene, other facultative symbionts may remain undetected in natural populations of A. thunbergii. The high levels of symbiont coinfections in A. thunbergii (Table 3) are striking but not exceptional: a number of recent studies have revealed frequent coinfections with multiple symbiotic bacteria in natural insect populations (40)(41)(42)(43).…”
Section: Resultsmentioning
confidence: 99%